Sistem Pendukung Keputusan Rekomendasi Pembelian Perumahan Menerapkan Metode MOORA - Juanda Hakim Lubis; Mesran Mesran; Salsabila Edrin; Afriyani Nasution (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Housing is a secondary need. For the selection of the right housing, it must be adjusted to the wishes of consumers. When selecting housing or determining where to live, consumers must look for brochures and visit housing sales sites, and do not choose housing at random just because friends or other people offer it, because this can cause regret because it is not in accordance with which are desired. To assist prospective buyers in making housing buying decisions, we need a decision support system that will assist prospective buyers in choosing the desired housing. In order to get the best results, we need a system that can help determine the house in such a way that consumers are satisfied. Multi-Objective Optimization on the basis of Ratio Analysis (MOORA) is a method provided by SPK to facilitate housing selection because this method has good selectivity in determining different goals and criteria. After carrying out the calculations of the MOORA method, the final result is obtained which shows that the alternative with the highest Yi value is A1 with a Yi value of 0.282. In the second rank, there is alternative A2 with a Yi value of 0.277, while the third rank is occupied by alternative A5 with a Yi value of 0.263. Therefore, based on predetermined criteria, alternative house A1 can be considered as the best option.